A SEDUÇÃO DA LUZ: ELETRIFICACÃO E IMAGINÁRIO NO RIO DE JANEIRO DA BELLE ÈPOQUE. (Revista de História Regional, 2007)
One of the recurent symbols wich represents the city of Rio de Janeiro at the turn of the 20th century was electrification. These representations were rich in meaning and they also had a social and historical sense besides being linked to a collective imaginary, wich has one of the most important embodiment in the modernisation process.Só, the aim of this study is to analyse this process, based on an approach from the imaginary. Our intention is to examine the way wich the modernity seduction - or the light seduction - implies in a set of values which are able to organize life in society.